Time-saver standards for building types - De Chiara, Joseph (McGraw-Hill Book, 1973)
Includes bibliographical references and index.; Save time with topic-by-topic guide to building standards The only comprehensive reference to all building types, Time-Saver Standards for Building Types, Fourth Edition is loaded with all the essential design criteria and standards you need to prepare preliminary designs, execute programming requirements, and analyze the functions and uses of a building. Authors Joseph DeChiara and Michael Crosbie focus on topical issues of rehabilitation, change of use, preservation, accessibility, energy conservation, and environmental regulations. New material in this edition includes home offices, entertainment centers, assisted living, primary-care and wellness facilities, day-care and nursery facilities, jails and prisons, places of worship, health clubs, international sports facilities, and new rail facilities. What's more, new international examples and full metrification make the book a truly global publication